A green eco-environment for sustainable development: framework and action - Xuejun LIU, Wen XU, Zhipeng SHA, Yangyang ZHANG, Zhang WEN, Jingxia WANG, Fusuo ZHANG, Keith GOULDING (Frontiers of Agricultural Science and Engineering, 2020)
Following its 40-year reform and 'Open Door' policy, China has recently proposed a new approach to green development and rural revitalization—the idea of Agriculture Green Development (AGD), with the key feature of creating a green eco-environment. In this mini-review we introduce the definition, theory, framework and major components of a green eco-environment as a key part of the AGD. We define a green eco-environment as including four key elements or measures: (1) a green eco-environmental indicator system; (2) environmental monitoring and warning networks; (3) emission standards and environmental thresholds for key pollutants; (4) emission controls and pollution remediation technologies. We have used Quzhou County (a typical county in the center of the North China Plain) as an example to show how detailed air, water and soil monitoring networks, as well as improved farmer practices and pollution control measures (especially ammonia emission mitigation and PM2.5 pollution reduction), can begin to create a green eco-environment in China and that AGD is possible. We conclude by stressing the need to improve the framework and practice for a green eco-environment, especially the importance of linking proposals and practices for a green eco-environment with the United Nations high priority Sustainable Development Goals.